H. Pylori Fecal Antigen Detection taking endoscopic biopsy as gold standard in Dyspeptic Patients - Shafaq Farooq, Muhammad Aslam, Muhammad Arif, Umar Farooq, Nasim Akhtar, Lubna Meraj, Shafaq Farooq, Muhammad Aslam, Muhammad Arif, Umar Farooq, Nasim Akhtar, Lubna Meraj (Journal of Rawalpindi Medical College, 2022)
Introduction: There are several invasive and non-invasive techniques used to diagnose H. pylori infection, each having its own advantages and disadvantages. Invasive methods require biopsy samples from stomach and duodenum and can be tested by various methods such as histology, Rapid urease test (RUT), microbiological culture and Polymerase chain reaction (PCR) whereas non-invasive tests include stool antigen test, serology and Urea breath test Objectives: To determine the diagnostic accuracy of H. Pylori Fecal Antigen Detection taking endoscopic biopsy as gold standard in dyspeptic Patients (18-65 years). Materials & Methods: Descriptive, cross-sectional study was conducting during 30th April 2019 to 30th October 2019 in Gastroenterology Unit, Holy Family Hospital, Rawalpindi. A total of 85 patients irrespective of gender having age 18-65 years having symptoms of dyspepsia were included. Patients having gall stones, celiac disease, pancreatic disease, Diabetes Mellitus, thyroid disease and any other patients on PPI or H2 receptors. Patients with history of alcoholism, diagnosed cases of H. Pylori infection or treatment history of H Pylori. Patients diagnosed for pancreatitis, cholecystitis, Hepatitis B or C Virus positive cases of Chronic Liver Diseases, HIV, malignancy or Ischemic Heart Disease or being pregnant were excluded. H. Pylori on Fecal Antigen Detection and endoscopic biopsy were noted. Results: Fecal Antigen Detection found that 42 were True Positive and 04 were False Positive. Among 39, Fecal Antigen negative patients, 04 (False Negative) had H. Pylori on endoscopic biopsy whereas 35 (True Negative) had no H. Pylori involvement on endoscopic biopsy (p=0.0001). Overall sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of H. Pylori Fecal Antigen Detection taking endoscopic biopsy as gold standard in dyspeptic Patients was 91.30%, 89.74%, 91.30%, 89.74% and 90.59% respectively. Conclusion: This study concluded that diagnostic accuracy of H. Pylori Fecal Antigen Detection in dyspeptic Patients is quite high. Keywords: helicobacter pylori, Fecal Antigen Detection, endoscopic biopsy.